Les habitats du lac de Paladru (Isère) dans leur environnement La formation d'un terroir au XIe siècle - Colardelle, Michel; Verdel, Éric (Documents d'archéologie française, 1993)
This study, by M. Colardelle, E. Verdel and a team of forty researches, of a fortified-settlement constructed in 1003 AD and abandonned before being submerged under the water of Lake Paladru around 1040 AD, enlarged to cover the surrounding landscape, has made an essential contribution to archaeology and medieval history. Besides fundamental information concerning architecture in wood, arts and crafts, food supply and agriculture, of which the evidence was remarkably well preserved, this research has led to a new interpretation of the events leading up to the revolution of 1000 AD, a key period in the history of the West. Exceptional, considering the investigational techniques used (stratigraphical excavation in subaquatic conditions, environmental sciences and archaeometry) and the results obtained, this study is of interest to historians and naturalists, but also to those interested by the relationship between archaeology and history, the first producing unique evidence to support the second.